Scale Validity and Reliability of Social Media and Entrepreneurial Skill Development among Tertiary Institution Students in Nigeria - Suleiman, Yusuf; Hameed Olalekan, Bolaji; Mutiu Adekunle, Ganiyu; Adam Ishola, Mustapha; Abdulrasheed, Jimoh (Journal of Technology Management and Business, 2020)
Social media has gained broader acceptability and usability and is fast becoming perhaps the most important communication tool in 21st Century. The acceptability of the social media has gained tremendous popularity among students especially at higher institution. Drawing from the foregoing point, the main purpose of the study thus is to examine the validity and reliability of the instruments on the nexus between social media adoption and entrepreneurial skills development among tertiary institution students in Nigeria focusing on the pilot study report. For the purpose of the pilot study, 100 students were selected from Al-Hikmah University and Kwara State University in Kwara State because of their serious commitment to entrepreneurial skills development for the quantitative aspect, while two artisans each from the universities were used for data collection in qualitative approach. Two instruments were used to collect data. First, an instrument titled â€œSocial Media and Entrepreneurship Questionnaire (SMEQ)â€ was designed to get comprehensive information from the students. Second, an interview protocol tagged â€œInterview Protocol on Social Media Adoption and Entrepreneurship (IPMSAE)â€ was designed to elicit relevant information from the artisans. Both Statistical Package and Social Sciences (SPSS) and PLS-SEM Software were used to assess the psychometric properties of the adapted instruments. Also, thematic type of analysis was used to assess the credibility or otherwise of the interview protocol. Findings from qualitative approach reveal that Cronbachâ€™s Alpha of the instrument loaded between 0.821 and 0.942 (Social Media Adoption: 0.885; Social Media and Addictive Behavior: 0.821; Entrepreneurial Skills: 0.942 and Self-Reliance: 0.914). Also, the use of PLS-SEM shows that composite reliability, crossloadings, average variance extracted (AVE) and discriminant validity loaded within the minimum benchmarks, indicating adequate validity and reliability of the instrument. Furthermore, transcription, coding and analysis of the interview collected show the trustworthiness and credibility of the protocol. Based on the findings of the study, it can be advanced that the findings of the study helped to establish adequate validity and reliability of the instruments used via quantitative and qualitative methods adopted.